On the boundedness of operators in LP(ιq) and Triebel-Lizorkin Spaces - João Pedro Boto (Journal of Function Spaces and Applications)
Given a bounded linear operator T:LPO(ℝn)→Lp1(ℝn), we state conditions under which T defines a bounded operator between corresponding pairs of Lp(ℝn;ιq) spaces and Triebel-Lizorkin spaces Fp,qs(ℝn). Applications are given to linear parabolic equations and to Schrödinger semigroups.